PENGARUH KUALITAS PRODUK DAN MEREK TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PADA PT.INDOFOOD CBP SUKSES MAKMUR TBK) TANJUNG MORAWA - Bagus Handoko (JURNAL ILMIAH MANAJEMEN & BISNIS, 2015)
The company was running a business, either directly or indirectly affects the viability of the company. From the ANOVA or F test , obtained F count of 49.839 with a significance level of 0.000 . So F count > F table (49.839 >3,09) or sig F < 5% (0,000 <0,05). It means that the variable quality of products and brand  significantly the simultaneous influence towards the  customer loyalty (y).  By this it can be concluded that the hypothesis of this study can be proven .R-square for y ( customer loyalty ) is 0.526. This means that 52.6% of variation in customer loyalty (y) is influenced by the variable x1 ( product quality ) and variable x2 ( brand ) or influence product quality (x1) and brand (x2 ) collectively or synchronously to the variable y ( customer loyalty  ) amounted to 52.6 % and the balance of 47.4 % is determined by other variables .Due to the quality of products significantly affect the increase of customer loyalty , then the quality of the resulting  product is maintained and if necessary enhanced  through increasingly sophisticated technology so the results more satisfying consumer.  Keywords : Product Quality,Brand,Customer Loyality